Mutational signature distribution varies with DNA replication timing and strand asymmetry - Tomkova, Marketa (Genome Biol, 2018)
BACKGROUND: DNA replication plays an important role in mutagenesis, yet little is known about how it interacts with other mutagenic processes. Here, we use somatic mutation signatures—each representing a mutagenic process—derived from 3056 patients spanning 19 cancer types to quantify the strand asymmetry of mutational signatures around replication origins and between early and late replicating regions. RESULTS: We observe that most of the detected mutational signatures are significantly correlated with the timing or direction of DNA replication. The properties of these associations are distinct for different signatures and shed new light on several mutagenic processes. For example, our results suggest that oxidative damage to the nucleotide pool substantially contributes to the mutational landscape of esophageal adenocarcinoma. CONCLUSIONS: Together, our results indicate an interaction between DNA replication, the associated damage repair, and most mutagenic processes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s13059-018-1509-y) contains supplementary material, which is available to authorized users.